2012
DOI: 10.1097/gme.0b013e31822bda11
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported estrogen use and newly incident urinary incontinence among postmenopausal community-dwelling women

Abstract: OBJECTIVE To examine the relationship between self-reported estrogen use and newly-incident urinary incontinence (UI) among community-dwelling postmenopausal women. METHOD A population based longitudinal survey of postmenopausal women who did not report UI in 1993 and for whom complete data were available. Women were classified as having newly-incident UI if they reported uncontrolled urine loss within 12 months of the 2004 interview. Condition-specific functional loss secondary to UI was assessed by questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
(39 reference statements)
0
3
0
1
Order By: Relevance
“…Urogenital tissue may display sensitivity responses varying in accordance to different estrogen levels [5]. Decreased estradiol levels may cause bladder dysfunction and reduce uretral closure which may contribute or exacerbate an existing UI [3,4,6,7]. Despite this, several reports have failed to demonstrate that hormone therapy (HT) improves urinary symptoms (i.e.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Urogenital tissue may display sensitivity responses varying in accordance to different estrogen levels [5]. Decreased estradiol levels may cause bladder dysfunction and reduce uretral closure which may contribute or exacerbate an existing UI [3,4,6,7]. Despite this, several reports have failed to demonstrate that hormone therapy (HT) improves urinary symptoms (i.e.…”
Section: Introductionmentioning
confidence: 95%
“…Despite this, several reports have failed to demonstrate that hormone therapy (HT) improves urinary symptoms (i.e. incontinence, urge syndrome) in postmenopausal women [7][8][9][10][11]. Important to state is that subjective sensation related to UI does not always correlate with urodynamic findings [12].…”
Section: Introductionmentioning
confidence: 97%
“…The overall risk of UI remained low however, with an annual incidence of 1.6%, and the effects of HRT disappeared when treatment ceased.A recent cohort study of post-menopausal women found an association between UI symptoms and duration of oestrogen treatment. Prolonged oral oestrogen therapy (5 years or more) is associated with a worsening of leakage symptoms (OR = 3.99[1.21-13.1]) and also an increase in the frequency of handicapping UI (3.97 [1.02-15.4])[37] (LE3).…”
mentioning
confidence: 99%
“…Корреляция между симптомами недержания мочи и продолжительностью приема эстрогенов выявлена в ко-гортном исследовании женщин в постменопаузе [36]. Пролонгированный прием эстрогенов (более 5 лет) ассо-циировался с повышением риска развития недержания мочи (ОР=3,97 при 95% ДИ 1,02-15,4) и ухудшением те-чения симптомов заболевания (ОР=3,99 при 95% ДИ 1,21-13,1).…”
Section: треугольник льето 40unclassified